Applications and prospects of genome editing in plant fatty acid and triacylglycerol biosynthesis - Park, Mid-Eum; Kim, Hyun Uk (Frontiers in Plant Science, 2022)
Triacylglycerol (TAG), which is a neutral lipid, has a structure in which three molecules of fatty acid (FA) are ester-bonded to one molecule of glycerol. TAG is an important energy source for seed germination and seedling development in plants. Depending on the FA composition of the TAG, it is used as an edible oil or industrial material for cosmetics, soap, and lubricant. As the demand for plant oil is rising worldwide, either the type of FA must be changed or the total oil content of various plants must be increased. In this review, we discuss the regulation of FA metabolism by CRISPR/Cas9, a recent genome-editing technology applicable to various plants. The development of plants with higher levels of oleic acid or lower levels of very long-chain fatty acids (VLCFAs) in seeds are discussed. In addition, the current status of research on acyltransferases, phospholipases, TAG lipases and TAG synthesis in vegetative tissues is described. Finally, strategies for the application of CRISPR/Cas9 in lipid metabolism studies are mentioned.